A Synthetic Reporter for Probing Mistranslation in Living Cells - Chen, Hao; Ercanbrack, Carson; Wang, Tony; Gan, Qinglei; Fan, Chenguang (Frontiers in Bioengineering and Biotechnology, 2020)
Aminoacyl-tRNA synthetases (AARSs) play key roles in maintaining high fidelity of protein synthesis. They charge cognate tRNAs with corresponding amino acids, and hydrolyze mischarged tRNAs by editing mechanisms. Impairment of AARS editing activities can reduce the accuracy of tRNA aminoacylation to produce mischarged tRNAs, which cause mistranslation and cell damages. To evaluate the mistranslation rate of threonine codons in living cells, in this study we designed a quantitative reporter derived from the green fluorescent protein (GFP). The original GFP has multiple threonine codons which could affect the accuracy of measurement, so we generated a GFP variant containing only one threonine residue to specifically quantify mistranslation at the threonine codon. To validate, we applied this single-threonine GFP reporter to evaluate mistranslation at the threonine codon with mutations or modifications of threonine-tRNA synthetase and compared with other methods of mistranslation evaluation, which showed that this reporter is reliable and facile to use.